DC-MICROGRID DESIGN WITH PV HYBRID SYSTEM AND PLN NETWORKS FOR DC LOADS - Syafitri, Siska Rachma Putri (International Journal of Engineering and Emerging Technology; Vol 6 No 2 (2021): July - December 2021, 2022)
The microgrid system is an interconnected network system of various energy sources distributed into a small network that can operate independently or connected to the main network (PLN). The purpose of using the system microgrid is to create a more efficient method of generating electrical energy by utilizing renewable energy as a source of electrical energy. In this final project, a DC system microgrid with hybrid PV and PLN is made to supply a 12 V 19 W DC pump used in the pond. Two 50Wp PVs are installed in series and one 12V 33Ah lead acid battery is used as storage energy for PV output. Two 50 Wp PVs arranged in series are capable of producing a maximum voltage of up to 34 V when the irradiation value is above 1000 Wb/m 2 . With the use of PID control, the buck converter is able to reduce the PV output voltage from 34 V to a constant with an average output voltage of 13.798 V. The output of the buck converter is used as the value of the voltage charging on the battery. By doing test charging a battery close loop, the original battery voltage value was 12.48 V to 12.77 V with a charging time of 80 minutes. For the backup source, namely the PLN grid, used uncontrolled fullwave rectifier is as a rectifier from 220Vac to 24 Vdc. Because the required load voltage is 12 V, used voltage regulator is which regulates the output of the uncontrolled fullwave rectifier from 24 Vdc to 12 Vdc. The process switching between the PV source and the PLN grid source is carried out using the battery voltage value parameter. When the battery voltage value is more than 11.96 V the microcontroller will condition the main source relay (PV) to be ON and the backup source relay (PLN grid) is OFF, but when the battery voltage value is less than 11.96 V the microcontroller will condition the relay. the main source (PV) is OFF and the backup source relay (PLN) is ON.